1994
DOI: 10.1126/science.8036519
|View full text |Cite|
|
Sign up to set email alerts
|

Neutrophil and B Cell Expansion in Mice That Lack the Murine IL-8 Receptor Homolog

Abstract: Interleukin-8 (IL-8) is a proinflammatory cytokine that specifically attracts and activates human neutrophils. A murine gene with a high degree of homology to the two known human IL-8 receptors was cloned and then deleted from the mouse genome by homologous recombination in embryonic stem (ES) cells. These mice, although outwardly healthy, had lymphadenopathy, resulting from an increase in B cells, and splenomegaly, resulting from an increase in metamyelocytes, band, and mature neutrophils. Thus, this receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
421
3
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 625 publications
(447 citation statements)
references
References 24 publications
22
421
3
1
Order By: Relevance
“…Several studies showed that human PMN produced TNF-α, IL-12 and IL-8 after stimulation with microbial products such as bacterial LPS, Toxoplasma gondii and Candida albicans [10][11][12]. While human PMN normally undergo rapid apoptosis during culture, several inflammatory cytokines (e.g., IL-1β, TNF-α, IL-6, G-CSF, GM-CSF) prolong their life span [4,13].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that human PMN produced TNF-α, IL-12 and IL-8 after stimulation with microbial products such as bacterial LPS, Toxoplasma gondii and Candida albicans [10][11][12]. While human PMN normally undergo rapid apoptosis during culture, several inflammatory cytokines (e.g., IL-1β, TNF-α, IL-6, G-CSF, GM-CSF) prolong their life span [4,13].…”
Section: Discussionmentioning
confidence: 99%
“…CXCR2ko mice appear outwardly healthy, but previous studies have demonstrated that approximately 25% of these mice exhibited granulopoiesis in the periportal regions of the liver. 39 Although CXCR2ko mice do not normally exhibit hepatic damage, 39 the increased presence of granulocytes in the liver may partly account for the increased susceptibility of these mice to the lethal effects of acetaminophen. However, it should be emphasized that approximately 75% of the CXCRko mice examined in the present study died as a result of acetaminophen challenge.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative to knockout a chemokine gene in mice to study the role of the chemokine is to knockout the gene for a chemokine receptor. An example of this is the knockout of the human IL-8R homologue (murine [m]IL-8Rh -/-) in mice in which enhanced neutrophils and B-lymphocyte numbers were apparent [61]. These mIL-8Rh 4-mice had bone marrow cells responsive to inhibition by a number of chemokines including human MIP-la, PF4, P-10 and MCP-1, but they were insensitive to inhibition by human IL-8 1621: These results suggested that IL-8 may be mediating its suppressive effects through CXCR2 (IL-8RB).…”
Section: Inhibition Of Synergistically Stimulated Cell Proliferation mentioning
confidence: 99%